2008
DOI: 10.1021/ef800245z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyrolysis Intensity on the Reactivity of Coal Char

Abstract: The effect of pyrolysis conditions on char reactivity was studied in this paper. The char samples were prepared in a N2 atmosphere from the vitrinite constituents of two bituminous coals (YX and JJ) and their demineralized samples at different temperatures (800−1200 °C) and for different residence times. The effect of pyrolysis intensity on the carbon microstructure in the resulting char was characterized by the X-ray diffraction (XRD) technique. The reactivity of the char samples prepared under different pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…The structural parameters were found to be 2.08 and 1.08 for the inertenite-and vitrinite-rich chars, respectively, which depend on the initial properties of the chars, Equation (8). Since the limiting value for pore growth according to the random pore model is greater than a value of 2 [6,101,102,106,127] both chars can be considered to have experienced mainly pore growth and pore coalescence during the initial stage of the char-CO2 gasification reaction.…”
Section: Experimental Reactivity and Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…The structural parameters were found to be 2.08 and 1.08 for the inertenite-and vitrinite-rich chars, respectively, which depend on the initial properties of the chars, Equation (8). Since the limiting value for pore growth according to the random pore model is greater than a value of 2 [6,101,102,106,127] both chars can be considered to have experienced mainly pore growth and pore coalescence during the initial stage of the char-CO2 gasification reaction.…”
Section: Experimental Reactivity and Parametersmentioning
confidence: 99%
“…Substantial research have found that the chemical interactions between carbon molecules and reactant gases take place at the edge active carbon atoms for coal based char models and also for non-coal char models [3,28,39,43,60,64,[103][104][105], and Zhang et al found that the carbons in the basal plane of large, fused-ring aromatic domains of chars, were inert [106]. Figure 1 shows results from the HRTEM technique, which were used to derive the char models used here [45].…”
Section: Dft Reactivity Modelling and The Fukui Functionmentioning
confidence: 99%
See 3 more Smart Citations